Novel polyethyleneimine-R8-heparin nanogel for high-efficiency gene delivery in vitro and in vivo. (1st January 2018) - Song, Linjiang; Liang, Xiuqi; Yang, Suleixin; Wang, Ning; He, Tao; Wang, Yan; Zhang, Lan; Wu, Qinjie; Gong, Changyang
Abstract: Gene therapy is an efficient and promising approach to treat malignant tumors. However, protecting the nucleic acid from degradation in vivo and efficient delivering it into tumor cells remain challenges that require to be addressed before gene therapy could be applied in clinic. In this study, we prepared novel polyethyleneimine-RRRRRRRR(R8)-heparin (HPR) nanogel as an efficient gene delivery system, which consists of heparin and cell penetrating peptide R8 grafted low-molecule-weight polyethyleneimine (PEI). Due to the shielding effect of heparin, crosslinking PEI-R8 with heparin was designed to diminish the toxicity of the gene delivery system. Meanwhile, a partial of R8 peptide which located on the surface of HPR nanogel could significantly enhance the cellular uptake. The formed HPR/pDNA complex exhibited effective endolysosomal escape, resulting in a high-efficiency transfection. Furthermore, the HPR could deliver the plasmid which could transcribe human TNF-related apoptosis inducing ligand (phTRAIL), into HCT-116 cells and induce significant cell apoptosis. In addition, HPR/phTRAIL complex showed satisfactory antitumor activity in abdominal metastatic colon carcinoma model. Finally, the antitumor mechanism of HPR/phTRAIL was also explored by western blot and histological analysis. The above results suggested that the HPR nanogel could serve as a promising gene delivery system.